The effect of consumers’ food poisoning prevention knowledge, attitude, risk perceptions and environmental assessment on bought cooked food using partial least square structural equation model (PLS-SEM) - Awang Hamat, Rukman; Osman, Malina; Sekawi, Zamberi; Mamot, Masyita; Mohamed, Nurul Azmawati; Mohd Rani, Mohd Dzulkhairi (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2024)
This paper aims to investigate consumer knowledge, attitude, risk perceptions and environmental assessment of food safety and their direct effects on food poisoning preventive behaviour. Consumers play a crucial role in ensuring the safety of the food they consume, particularly when it comes to cooked food that is sold to them. Therefore, understanding consumers' knowledge, attitude, risk perceptions, and food safety environmental assessment is crucial in influencing their behaviour to prevent food poisoning. Materials and methods: We conducted a cross-sectional survey among 430 consumers aged 18 years and above around Ampang areas in Selangor using a validated Knowledge, Attitude, Practice, Perception and Environment (KAP2E) questionnaire. The questionnaires were self-administered among consumers and information on sociodemographic, food poisoning knowledge, attitude, risk perceptions and food safety environmental assessment were gathered. We used PLS-SEM to establish the relationship between the constructs under investigation. Results: The evaluation of the structural model indicates that knowledge, attitude, risk perceptions, and food safety environmental assessment account for 22.1% of preventive food poisoning preventive behaviour. Attitude was the strongest predictor (β= 0.381, p< 0.05) among other constructs. This study confirmed that food poisoning knowledge have positive impact on consumer’s attitude (R2 = 0.053).Conclusion: The present study highlights the importance of incorporating consumer risk perceptions and food safety environmental assessment into food safety education. By enhancing consumers' knowledge and attitude towards food poisoning prevention, we can ensure the effectiveness of these educational efforts.